Perbandingan Mekanisme Penentuan Ujroh Pembiayaan Gadai Emas Syariah di Bank BJBS dan Bank BSI - Wijaya, Trisna; Nasrulloh, Agus Ahmad (JURNAL EKONOMI SYARIAH, 2022)
Gold pawn financing is one of the financing that the public is interested in. the gold pawn financing has a lower risk than other financing product, because the collateral has been held by creditor, stable gold price and gold price tend to rise. With a low risk profile, several Islamic financial institutions are interested to provide this financing product, including BJB Sharia Bank and BSI Bank. The profit taken by the bank named ujrah. BJB Shariah Bank dan BSI bank has a different mechanism to calculate the ujrah. The rules regarding sharia gold pawn financing have been regulated in fatwa DSN-MUI number 25 in 2002 about rahn and number 26 in 2002 about gold rahn. This regulation should be used as the guideline for financial institutions that provides gold pawn financing.